Let f = 22 + -20. Suppose -d = -f*d. Suppose 0 = -2*t + 5*l + 5, -t + l = -11 + 1. Solve t = 5*z - d*z for z.

3

Let x be (6/(-5))/(3/(-10)). Solve -10 + x = -2*s for s.

3

Suppose -28*t = -31*t + 9. Solve w = t - 5 for w.

-2

Let b(j) be the third derivative of j510 - j424 - j36 + 3*j2. Let u be b(-1). Suppose -14 = -x - u. Solve 0 = w - 3*w - x for w.

-4

Let l® = -7*r - 14. Let x be l(-2). Solve x = -2*q + 4 + 4 for q.

4

Suppose 2*t - 4 = -4*j, 0*j = 5*j + 4*t - 8. Solve j*i - 1 = -i for i.

1

Let l(b) = -b**2 + 7*b - 4. Suppose 6*g - g + 33 = 3*m, 0 = -5*g - 15. Let v be l(m). Solve 15 = v*x - 5*x for x.

-5

Let x(z) be the third derivative of -z3 + 0*z + 4*z2 - 112*z**4 + 0. Let p be x(-4). Solve -p*v - v - 15 = 0 for v.

-5

Let y(x) be the first derivative of -x**2 - 7*x - 2. Let f be ((-3)/4)/((-2)/(-16)). Let k be y(f). Solve k*j + 0*j = -20 for j.

-4

Let q(k) be the second derivative of k36 + 7*k22 - 2*k. Let n be q(-5). Solve -x + n = -3*x for x.

-1